Plantar fascia calcification a sequelae of corticosteroid injection in the treatment of recalcitrant plantar fasciitis. (16th August 2013) - Fox, Thomas Peter; Oliver, Govind; Wek, Caesar; Hester, Thomas
Abstract : We report the case of a 72-year-old woman suffering with severe plantar fasciitis who received a therapeutic corticosteroid injection. Two-and-a-half years after the injection she developed a small calcified lump under the skin which subsequently caused ulceration and infection. She went on to develop a diabetic foot infection requiring an extended course of intravenous antibiotics.